A predictive model of hospitalization cost after cerebral aneurysm clipping. (12th January 2015) - Bekelis, Kimon; Missios, Symeon; MacKenzie, Todd A; Labropoulos, Nicos; Roberts, David W
Abstract : Background: Cost containment is the cornerstone of the Affordable Care Act. Although studies have compared the cost of cerebral aneurysm clipping (CAC) and coiling, they have not focused on identification of drivers of cost after CAC, or prediction of its magnitude. The objective of the present study was to develop and validate a predictive model of hospitalization cost after CAC. Methods: We performed a retrospective study involving CAC patients who were registered in the Nationwide Inpatient Sample (NIS) database from 2005 to 2010. The two cohorts of ruptured and unruptured aneurysms underwent 1:1 randomization to create derivation and validation subsamples. Regression techniques were used for the creation of a parsimonious predictive model. Results: Of the 7798 patients undergoing CAC, 4505 (58%) presented with unruptured and 3293 (42%) with ruptured aneurysms. Median hospitalization cost was US24 398 (IQR 17 079 to 38 249) and 73 694 (IQR 46 270 to 115 128) for the two cohorts, respectively. Common drivers of cost identified in the multivariate analyses included the following: length of stay, number of admission diagnoses and procedures, hospital size and region, and patient income. The models were validated in independent cohorts and demonstrated final R 2 values very similar to the initial models. The predicted and observed values in the validation cohort demonstrated good correlation. Conclusions: This national study identified significant drivers of hospitalization cost after CAC. The presented model can be utilized as an adjunct in the cost containment debate and the creation of data driven policies.